Traditional culture of settlements associated with the natural environment: the case of Yi minority Southwest China - Likai Lin; Yan Gui (Journal of Asian Architecture and Building Engineering, 2025)
Traditional culture of settlement is an important medium to record the process of balance between human and nature, and it was passed down from generation to generation in different forms (e.g. sacrificial culture, social structure, belief worship). With the intensification of global multicultural integration, the integration relationship between culture and nature has become an important approach for the protection and inheritance of traditional culture. Now, the relationship between artistic creation and ecological environment has been extensively studied. The scientific consensus regarding the influence of ecological environment on artistic creation has gained widespread recognition. Nevertheless, previous research neglects the relationship of traditional culture and natural environment, as well as different spatial characteristics, which are closely related to agricultural production and living. Based on the in-depth investigation of 23 traditional settlements of Yi minority in Southwest China, this paper conducted spatial analysis based on aerial photography, satellite maps and field investigation to analyze the relationship of culture-environment-space. Our results showed that there are significant differences in settlement space (e.g. landscape pattern, landscape space, architectural form) of Yi minority distributed in different areas. Under the same cultural background, the dispersed layout appears in Liangshan with high altitude and cold climate; the mountain foot layout appears in Central Yunnan and Northwest Guizhou with flat terrain and mild climate; the centralized layout appears in Honghe with narrow valleys and hot climate. These results shows that traditional culture comes from the natural environment, and the settlement space built under the guidance of the traditional culture must be in harmony with the natural environment. Therefore, protecting the traditional culture plays an important role in the sustainable development of urban and rural settlements. In addition, our findings may serve to inheritance and protection of traditional culture in other area all over the world.